Telaah Metodologis Kitab Tafsir Irsyad al-‘Aql al-Salim Ila Mazaya al-Kitab al-Karim Karya Abu al-Su’ud Al-‘Imadi - Muhammad Hafizh Basyiruddin; Sandi Nugraha; Eni Zulaiha (Faculty of Ushuluddin UIN Sunan Gunung Djati Bandung, 2023)
The purpose of this paper is to analyze Abu al-Su'ud Al-'Imadi's exegetical manual, Irsyad al-'Aql al-Salim ila Mazaya al-Kitab al-Karim, focusing on the manual's sources of interpretation (mashdar), techniques of interpretation (manhaj), and interpretation orientation (ittijah). The mufassir's life story, his scientific discoveries, and the context of the commentary's composition are all briefly covered. This method of research is qualitative and takes a literature-based approach. From the perspective of the source, Abu al-Su'ud Al-'Imadi's commentary Irsyad al-'Aql al-Salim ila Mazaya al-Kitab al-Karim falls into the category of interpretation bi al-Ra'yi; from the perspective of the method, it employs the tahlili; and from the perspective of the orientation, it includes the lughawi. Abu al-Su'ud al-'Imadi was a scholar who lived during the Ottoman Empire's golden age, when the population enjoyed economic success, political stability, and scientific advancement. This seems to be the driving force behind Abu al-interpretation Su'ud's from a linguistic perspective. His ardor for the Arabic language and literature, which has elevated him to the level of an expert in the field, is another important factor in the linguistic focus of his interpretations (lughawi).